The Effect of Religiosity On Tax Evasion Behavior With Gender as a Moderating Variable - Illahi, Ilham; Sumari, Nini (IAIN Surakarta, 2021)
Tax evasion is a form of non-compliance by taxpayers in paying taxes. Tax evasion behavior must be mitigated so that the country's economic growth can grow well. This study examines the effect of religiosity on tax evasion. To expand the test, the researcher included gender as a moderating variable. The object of this research is the students of the Islamic Economics and Business Faculty (FEBI) of IAIN Bukittinggi. The selection of this sample is based on the students of FEBI IAIN Bukittinggi who will enter the business world so that in the future they will become taxpayers. Through Moderated Regression Analysis (MRA) testing was conducted to see the effect of gender variables in moderating the relationship between tax evasion and religiosity. The results of this study found that the level of student religiosity had no impact on reducing tax evasion. However, this study supports the findings of previous studies where gender has different reactions to tax evasion, female students are more likely to avoid tax evasion than male students. Keywords: Tax Evasion, Religiosity, Gender, Taxpayers